A nonfunctional sequence converted to a signal for glycophosphatidylinositol membrane anchor attachment (The Rockefeller University Press, 1991)
The COOH terminus of decay-accelerating factor (DAF) contains a signal that directs glycophosphatidylinositol (GPI) membrane anchor attachment in a process involving concerted proteolytic removal of 28 COOH- terminal residues. At least two elements are required for anchor addition: a COOH-terminal hydrophobic domain and a cleavage/attachment site located NH2-terminal to it, requiring a small amino acid as the acceptor for GPI addition. We previously showed that the last 29-37 residues of DAF, making up the COOH-terminal hydrophobic domain plus 20 residues of the adjacent serine/threonine-rich domain (including the anchor addition site), when fused to the COOH terminus of human growth hormone (hGH) will target the fusion protein to the plasma membrane via a GPI anchor. In contrast, a similar fusion protein (hGH-LDLR-DAF17, abbreviated HLD) containing a fragment of the serine/threonine-rich domain of the LDL receptor (LDLR) in place of the DAF-derived serine/threonine-rich sequences, does not become GPI anchored. We now show that this null sequence for GPI attachment can be converted to a strong GPI signal by mutating a pair of residues (valine-glutamate) in the LDLR sequence at a position corresponding to the normal cleavage/attachment site, to serine-glycine, as found in the DAF sequence. A single mutation (converting valine at the anchor addition site to serine, the normal acceptor for GPI addition in DAF) was insufficient to produce GPI anchoring, as was mutation of the valine- glutamate pair to serine-phenylalanine (a bulky residue). These results suggest that a pair of small residues (presumably flanking the cleavage point) is required for GPI attachment. By introducing the sequence serine-glycine (comprising a cleavage-attachment site for GPI addition) at different positions in the LDLR sequence of the fusion protein, HLD, we show that optimal GPI attachment requires a processing site positioned 10-12 residues NH2-terminal to the hydrophobic domain, the efficiency anchor attachment dropping off sharply as the cleavage site is moved beyond these limits. These data suggest that the GPI signal consists solely of a hydrophobic domain combined with a processing site composed of a pair of small residues, positioned 10-12 residues NH2- terminal to the hydrophobic domain. No other structural motifs appear necessary.